PERCEIVED EFFECTIVENESS OF GRAMMARLY AND QUILLBOT IN SUPPORTING ENGLISH WRITING SKILLS - Bahing; Mayang Meilantina; Bahing Bahing (Bajang Institute, 2026)
This study aims to analyze students’ perceptions of using Grammarly and QuillBot in writing at MA Annur Teluk Palinget. This research employed a mixed-methods approach with a convergent parallel design. The population consisted of 95 students, with 65 students selected as the sample and 9 students involved in interviews. Data were collected through questionnaires and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. The findings show that students have highly positive perceptions of both tools, with an identical mean score of 3.85 categorized as “very positive.” Accessibility received the highest agreement (97%), indicating that flexibility and ease of use strongly influence students’ engagement. Both tools were perceived as effective in providing feedback and improving grammar, particularly in sentence structure and subject-verb agreement, although difficulties in tense usage remain. Grammarly is mainly used for grammar correction, while QuillBot supports paraphrasing and sentence variation. Overall, both tools complement each other in enhancing writing development in EFL contexts